KONTRIBUSI MUI DALAM REKONFIGURASI SYARIAH DI INDONESIA: (Melacak Peran dan Upaya MUI dalam Birokratisasi Syariah di Indonesia) - Moch. Nurcholis (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2020)
This research describes the contribution of MUI in the reconfiguration of sharia in Indonesia, from being an unwritten law to a binding law. MUI's efforts in reconfiguring sharia are carried out through the bureaucratization of sharia, namely the process of incorporation of sharia into national law which at an empirical level has been lived and carried out by the Muslim community in Indonesia. In contrast to the process of shariatisation or law Islamization which presupposes the replacement of national law with religious law, sharia bureaucratization is the work of labeling sharia law in legislation as an effort to guarantee legal certainty, administrative order, and achieve justice in legal disputes. The significance of the MUI's contribution in the effort to reconfigure Islamic law is evidenced by the issuance of statutory regulations sourced from fatwa products. Reconfiguration efforts are carried out in three ways, namely; First, to provide support for the birth of certain laws and regulations; Second, provide critical support and correction to a statutory regulation; Third, give a sharia fatwa.